The Efficacy and Safety of Vertebral Augmentation: A Second ASBMR Task Force Report. (24th January 2019) - Ebeling, Peter R; Akesson, Kristina; Bauer, Douglas C; Buchbinder, Rachelle; Eastell, Richard; Fink, Howard A; Giangregorio, Lora; Guanabens, Nuria; Kado, Deborah; Kallmes, David; Katzman, Wendy; Rodriguez, Alexander; et al.
ABSTRACT: Vertebral augmentation is among the current standards of care to reduce pain in patients with vertebral fractures (VF), yet a lack of consensus regarding efficacy and safety of percutaneous vertebroplasty and kyphoplasty raises questions on what basis clinicians should choose one therapy over another. Given the lack of consensus in the field, the American Society for Bone and Mineral Research (ASBMR) leadership charged this Task Force to address key questions on the efficacy and safety of vertebral augmentation and other nonpharmacological approaches for the treatment of pain after VF. This report details the findings and recommendations of this Task Force. For patients with acutely painful VF, percutaneous vertebroplasty provides no demonstrable clinically significant benefit over placebo. Results did not differ according to duration of pain. There is also insufficient evidence to support kyphoplasty over nonsurgical management, percutaneous vertebroplasty, vertebral body stenting, or KIVA®. There is limited evidence to determine the risk of incident VF or serious adverse effects (AE) related to either percutaneous vertebroplasty or kyphoplasty. No recommendation can be made about harms, but they cannot be excluded. For patients with painful VF, it is unclear whether spinal bracing improves physical function, disability, or quality of life. Exercise may improve mobility and may reduce pain and fear of falling but does not reduce falls or fractures in individuals with VF. General and intervention‐specific research recommendations stress the need to reduce study bias and address methodological flaws in study design and data collection. This includes the need for larger sample sizes, inclusion of a placebo control, more data on serious AE, and more research on nonpharmacologic interventions. Routine use of vertebral augmentation is not supported by current evidence. When it is offered, patients should be fully informed about the evidence. Anti‐osteoporotic medications reduce the risk of subsequent vertebral fractures by 40–70%. © 2018 American Society for Bone and Mineral Research.